The Recipient Vessel Hemodynamic Features Affect the Occurrence of Cerebral Edema in Moyamoya Disease After Surgical Revascularization: A Single-Center Retrospective Study - Xu, Liang; Li, Yin; Tong, Yun; Hu, Jun-wen; He, Xu-chao; Fu, Xiong-jie; Zhou, Guo-Yang; Cao, Yang; Yu, Xiao-bo; Zhou, Hang; Xu, Chao-ran; Wang, Lin (Frontiers in Neurology, 2022)
Objective In moyamoya disease (MMD) with direct or combined revascularization, the initially hemodynamic recipient features are likely one of the main causes of acute hemodynamic disruption. Previous studies have explored the relationship between recipient diameter or flow velocity and postoperative complications, but there are still no optimal selection criteria with multiple potential recipient vessels. Cerebral edema is one of the most common radiological manifestations in the acute postoperative period. This study assessed the hemodynamic characteristics of cortex vessels related to postoperative cerebral edema. Methods All patients who had undergone direct or combined revascularization with preoperative digital subtraction angiography (DSA) between 2019 and 2021 were eligible for inclusion in this study. The application of DSA was performed and regular radiological examinations were employed after surgery. DSA was analyzed with the hemodynamic features within chosen recipient vessels. Cerebral edema was identified as a low-density image on CT or high signaling in the MRI T2 phase. The recipient hemodynamic characteristics and demographic presentation, as well as clinical data, were retrospectively analyzed in this study. Results A total of 103 patients underwent direct or combined revascularization with preoperative DSA. The mean age of this enrolled cohort was 44.31 ± 10.386 years, in which bilaterally involved MMD accounted for the main part. The preliminary correlation analysis found preoperative disease period (p = 0.078), recipients observed in angiography (p = 0.002), and surgery on the left (p = 0.097) may be associated with cerebral edema. The following regression analysis confirmed low occurrence of cerebral edema was accompanied by recipients observed in angiography (p = 0.003). After subdividing by flow direction and hemodynamic sources, the incidence rate of anterograde direction, anterior sources, and posterior sources were significantly lower than undetected recipients. Conclusions Cerebral edema is a common radiological manifestation in MMDs after surgery. In this study, the observation in angiography reliably identifies a variety of physiological or pathological recipient detection, flow direction, and hemodynamic sources in patients with MMD after revascularization, which indicates the selection strategy of potential recipients and highlights the importance of recipient observability in DSA. Meanwhile, vascular conditions determined by recipient hemodynamics meditate the occurrence of postoperative cerebral edema.